ANALISIS KESTABILAN LERENG UNTUK PENANGANAN GERAKAN TANAH DENGAN METODE GROUTING DI PERUMAHAN BUKIT MANYARAN PERMAI (BMP) KOTA SEMARANG - Yones Lenardo Angelo (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2014)
Build an infrastructure must consider the aspects of geology in order to get maximum results. One of the geological aspects that must be considered is the condition of lithology. If the lithology is not sturdy, it will frequently moves or called landslide. This land movement can have negative impacts on existing communities in the vicinity.In this study, the author took the theme, slope stability analysis, which is located in Bukit Manyaran Permai Housing (BMP), Semarang. The housing have high intensity of damage due to soil movement. The housing is standing on ground that is dominated by clay. Clay has a low degree of friction angle and low cohesion so it will easily move if given more weight than the carrying capacity of the lithology.The methodology is using slope stability analysis computionally. The first step of research conducted by geotechnical mapping to determine the distribution of the existing surface lithology and clasify the damage of infrastructure caused by the movement of existing soil. Then drill in two different drill point where each point was drilled to a depth of 10 m. From the drilling results will be obtained samples to be used in laboratory testing, including unit testing and direct shear weight. From both test, the results will be obtained are the value of the unit weight, cohesion and friction angle which we can use for making modeling and computational search for the safety factor. In doing modeling and find the value of the safety factor of the location of the study authors using Slide 6.0 software which is very helpful in determining the value of the safety factor on the ground.From the computational analysis found that is worth the value of the safety factor of less than 1.5, it indicates the condition of the slopes of the potential occurrence of landslide. Therefore, at the end of this final report the authors provide proper recommendations handling of landslide in accordance with the results of laboratory analysis and the existing conditions in the field.